2012
DOI: 10.1093/eurjhf/hfr164
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic quantification of regional deformation helps to distinguish isolated left ventricular non‐compaction from dilated cardiomyopathy

Abstract: AimsPronounced trabeculation is presented in both left ventricular non-compaction (LVNC) and dilated cardiomyopathy (DCM), which sometimes makes the differentiation difficult. We hypothesized that echocardiographic deformation analysis would help to differentiate these two cardiomyopathies. Methods and resultsWe investigated 15 patients with LVNC (9 males; 42 + 9 years), 15 age-and gender-matched DCM patients, and 15 healthy controls. The echocardiographic diagnosis of LVNC was confirmed by magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
19
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 35 publications
9
19
1
4
Order By: Relevance
“…In our experience, none of the standard LV systolic dysfunction parameters was able to discriminate a DCM from a LVNC. Previous studies tried to find useful echocardiographic discrepancies and demonstrated the same results [18]. According to Tufekcioglu et al, we found that most of the conventional echocardiography findings for the two conditions were statistically similar [19].…”
Section: Discussionsupporting
confidence: 66%
“…In our experience, none of the standard LV systolic dysfunction parameters was able to discriminate a DCM from a LVNC. Previous studies tried to find useful echocardiographic discrepancies and demonstrated the same results [18]. According to Tufekcioglu et al, we found that most of the conventional echocardiography findings for the two conditions were statistically similar [19].…”
Section: Discussionsupporting
confidence: 66%
“…Patient with LVNC suggested on 2D echocardiography (B1), demonstrated reduction in longitudinal strain at the site of greatest trabeculation (apex) on a 2D speckle-tracking polar map (B2) and absent LV torsion as a result of unidirectional rotation of the base and apex (B3) (normally, basal rotation is clockwise while apical rotation is counter-clockwise). The apical versus base strain difference has been previously validated with tissue Doppler-based strain analysis 33. We have demonstrated the same with speckle tracking-based strain in panel B2.…”
Section: Cardiovascular Imaging Criteriasupporting
confidence: 62%
“…Recently, myocardial strain values have been shown to be abnormal in patients with LVNC even in the context of preserved systolic function32 (see supplement movie 1, figure A) suggesting subclinical LV dysfunction. Also, a pattern of relative basal sparing (ie, higher proportional reduction in strain in the apex compared with the base) has been shown to differentiate LVNC from dilated cardiomyopathy33 (figure 2B1,B2). In addition, more advanced mechanical parameters, such as basal and apical twist both occurring in the same direction, have also been shown to help differentiate LVNC from DCM34 (figure 2B3).…”
Section: Cardiovascular Imaging Criteriamentioning
confidence: 97%
“…Although several case reports have been published of this syndrome complicated with LVNC or DOMV alone, the combination of both complications has not been reported previously [3,4]. LVNC is characterized by the persistence of embryonic myocardial morphology and thickening of LV wall in the apical segments, due to noncompacted myocardium with prominent trabeculations [5]. LVNC is associated with heterogeneous genetic background, although the presence of any correlation with Sotos syndrome has not been firmly established [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Sotos syndrome should be screened for mitral valve anomaly, subvalvular apparatuses, and LV myocardial abnormality and function due to the reported wide variability of cardiac symptoms [5,6].…”
Section: Discussionmentioning
confidence: 99%